Compressor technology advances : beyond 2020 - Elliott, Hurlel; Bloch, Heinz P., 1933- (De Gruyter, 2021)
This book describes fresh approaches to compression technology. The authors describe in detail where, why, and how these can be of value to process plants. As such plants have become ever larger and more complex, more technology-intensive solutions have had to be developed for process machinery. The best practices that have emerged to address these requirements are assembled in this book.